Distribution Characteristics of Phenanthrene in Wheat, Soybean and Maize Leaves. (31st December 2021) - Sheng, Yu; Yu, Luyi; Shen, Yu; Gu, Ruochen; Li, Jinfeng; Sun, Fengfei; Zhan, Xinhua
Abstract: The pollution of polycyclic aromatic hydrocarbons (PAHs) in food crops has been drawing worldwide attention due to their toxicity and carcinogenicity. However, the distribution process of PAHs in crop leaves is not clear. Here, we firstly study the distribution of phenanthrene in wheat, soybean and maize seedling leaves. High performance liquid chromatography was used to determine phenanthrene concentration in crop leaves. Over the exposure time, phenanthrene concentration in young and mature leaves of wheat and soybean increased to the maximum at 72 h, which were 8.25 and 1.47 mg kg −1, and 5.91 and 3.02 mg kg −1, respectively, and phenanthrene concentration of young leaves was higher. Inversely, phenanthrene concentration in maize mature leaves was the highest and that in the second leaves was the lowest. The distributions of phenanthrene concentration in leaf base, leaf medium and leaf apex of the three crops were as follows: it was leaf medium > leaf base > leaf apex in wheat; it was same for soybean and maize, with leaf apex > leaf medium > leaf base. Phenanthrene concentrations of leaf edge in wheat, soybean and maize were 10.55, 3.88 and 18.96 mg kg −1 at 72 h, which were higher than those of leaf middle (10.21, 3.39 and 10.47 mg kg −1 ), respectively. Phenanthrene concentrations of mesophylls and veins increased with time, and phenanthrene concentration of veins was higher. The observation of two-photon fluorescence microscopy showed that phenanthrene was mainly accumulated near the vascular bundles of major vein. Accordingly, distribution of phenanthrene in crop leaves depends on the type of crop, growth period, and contribution of xylem and phloem to acropetal transport. Our results are helpful not only for better understanding the distribution of PAHs in crop leaves, but also for effectively controlling the translocation of PAHs into the leaves to ensure the safety of agricultural products.